Asthma prevalence is increased in patients with high metabolism scores for visceral fat: study reports from the US - Liu, Qiushi; Han, Xiaoxiao; Chen, Yan; Gao, Ying; Yang, Wei; Huang, Lewei (Frontiers in Endocrinology, 2023)
Methods： We assessed the association between METS-VF and asthma disease using multiple logistic regression analysis from the National Health and Nutrition Examination Survey (NHANES), 2001-2018, followed by subgroup analysis for sensitive populations. To determine whether METS-VF and asthma disease had a non-linear relationship, smooth curve fitting was used, and threshold effect analysis was used to verify the relationship. Results：Among the 36,876 participants, 4,919 self-reported having asthma. When all confounders were controlled for, a positive association was found between METS-VF and asthma prevalence (OR = 1.27, 95% CI: 1.22,1.32), and this positive association was stronger with elevated METS-VF (P for trend = 0.01). According to the smooth curve fitting analysis, METS-VF and asthma prevalence do not have a linear relationship. The double-segmented threshold effect analysis suggested a negative correlation but no statistically significant difference between METS-VF less than 5.24 and asthma prevalence (OR = 0.60, 95% CI: 0.33, 0.91). Besides, other METS-VF showed positive associations with asthma prevalence before and after the effective inflection point. According to subgroup analysis, METS-VF is associated with asthma prevalence among participants aged 40 – 59, male, Mexican American, with hypertension and diabetes, and without asthma history. Conclusion: A higher METS-VF is associated with a higher asthma incidence in a non-straight positive manner, and participants with a METS-VF above 5.24 should be cautious of a higher risk for asthma. The relationship should be given more attention to participants who are aged 40-59 years old, male, Mexican American, have hypertension, diabetes, and who do not have a family history of asthma.